2020
DOI: 10.1186/s40985-019-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

The health status of the early care and education workforce in the USA: a scoping review of the evidence and current practice

Abstract: Background: More than two million early care and education (ECE) providers care for young children in the USA each day. These providers tend to earn low wages and many are enrolled in public assistance programs. Nearly all ECE providers are female and they are disproportionately women of color. Despite the fact that these attributes place the ECE workforce at greater risk of chronic disease, the health status of the workforce is not established and the availability and effectiveness of interventions to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…In particular, it is not clear that the findings here can be generalized to other populations. The current study participants self-identified as female, which is consistent with the early childhood field as a whole (Lessard et al, 2020). However, it is possible that an important perspective is missing from men who work in early childhood settings.…”
Section: Limitations and Future Directionssupporting
confidence: 69%
“…In particular, it is not clear that the findings here can be generalized to other populations. The current study participants self-identified as female, which is consistent with the early childhood field as a whole (Lessard et al, 2020). However, it is possible that an important perspective is missing from men who work in early childhood settings.…”
Section: Limitations and Future Directionssupporting
confidence: 69%
“…Similarly, a 2017 Arkansas workforce study reported that 33% of their sample of ECE teachers were at risk for depression, and 40% reported being food insecure [ 9 ]. A 2020 scoping review on the health status of the U.S. ECE workforce and health-promoting interventions targeting this population further validated that this workforce experiences significant mental health challenges, including stress and depression, and has a heightened chronic disease risk due to suboptimal health behaviors, regardless of ECE setting (e.g., federally funded Head Start Programs for low-income households vs. for-profit or non-profit childcare centers) and job title [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…When examining the ECE workforce beyond the U.S., research shows that workplace stress is common among workers in other countries [ 22 ]. ECE workers in other countries, such as Singapore, also experience low pay, high turnover rate, and poor prestige [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 2 million early care and education (ECE) providers, mostly women, provide care to over 10 million preschool-age children in the US (1). As adults who take care of children for a substantial part of the day, they model and cultivate healthy eating behaviors essential to children's long-term health and behavior outcomes (2,3). Therefore, the health and well-being of ECE providers are essential to a child's early learning and development success (2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the health and well-being of ECE providers are essential to a child’s early learning and development success ( 2 ). However, ECE providers are susceptible to poor diet quality, sedentary lifestyle, stress, and economic worry ( 4 ) because they are more likely to live in poverty than, for example, K-12 teachers ( 5 ), earn low wages (national median wage = $24,230) ( 6 ), are often uninsured, and lack support and flexibility in their work environment ( 1 ).…”
Section: Introductionmentioning
confidence: 99%